A Nonlinear Dynamic Current Deviation Control Method for Suppressing Continuous Commutation Failures in UHVDC Systems - Bo YUAN; Ying WANG; Hua SHAO; Qianmao ZHANG; Liangdong QIN; Ningning LIU; Zhihui DAI (Zhongguo dianli)
Aiming at the continuous commutation failures in LCC-HVDC systems, a nonlinear dynamic current deviation control method is proposed. The operation curve of current deviation controller is dynamically adjusted according to the severity of AC faults. Meanwhile, the nonlinear curve is used to replace the original linear curve to improve both the sensitivity of extinction angle increment to the current deviation, and the actual extinction angle margin, thus effectively suppressing the commutation failures of DC systems. The simulation results in PSCAD/EMTDC show that the proposed control method can effectively suppress the continuous commutation failures caused by various faults and can help the rapid recovery of DC system after faults.